Alternative Modernity and Its Strategies - Gelūnas, Arūnas (Problemos, 2000)
The article deals with the fundamental problems in philosophy and humanities that Modernity has brought about: the split between facts and values, the weakening of interpersonal ties in society, the formation of the scientific-technological enterprise and the resulting shifts in the self-consciousness of the individuals. Most of the outstanding critics of Modernity – Stephen Toulmin, Leszek Kolakowski, Friedrich August von Hayek and Louis Dumont – argue that Cartesian rationality and its “byproduct”, rigid geometrical paradigm of knowledge, has to be replaced by a more flexible and evolution-oriented biological paradigm. Truth is said to be more of a local and “parochial” than of universal character – that is why one has to take seriously the multiplicity of customs and traditions instead of trying to check their rightness or wrongness by means of Cartesian Method. Scientific truth is valid within the limits of its own context. According to Evandro Agazzi, it is exceeding these limits and claiming the universal monopoly of truth that makes science become scientism – the scientific ideology instead of a method in service of human interests. The final part of the article presents some aspects of the reactions to modern science and rationality by a Non-Western society, namely that of Meiji Japan. The philosophy of “first Japanese philosopher” – Kitaro Nishida – is briefly examined.